2022
DOI: 10.18235/0004294
|View full text |Cite
|
Sign up to set email alerts
|

Brazil: Ministry of the Economy: Analysis of Key Functions and their Operational Macroprocesses: Benchmarking Operational Macroprocesses with Experiences from Canada, France, Peru, Spain, the United Kingdom, and the United States

Abstract: This technical note benchmarks Brazils Ministry of the Economy (ME) value chains and macroprocesses against relevant management models and practices used by ministries of finance, economy, or equivalent in selected Latin American and Organization for Economic Co-operation and Development (OECD) countries. This analysis, undertaken in the context of the creation of the ME by merging five former ministries, was intended to help identify gaps in current practices and propose recommendations for enhancing specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, the tradeoffs associated with any reorganization in government structures must be carefully assessed, as these changes entail costs, may create internal conflicts, and usually require time before the new structures are fully operational. (See Chapter 3 regarding Brazil's recent consolidation of several ministries in a unified Ministry of the Economy; Mosqueira, Lafuente, and Gaetani, 2022).…”
Section: Machinery Of Governmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the tradeoffs associated with any reorganization in government structures must be carefully assessed, as these changes entail costs, may create internal conflicts, and usually require time before the new structures are fully operational. (See Chapter 3 regarding Brazil's recent consolidation of several ministries in a unified Ministry of the Economy; Mosqueira, Lafuente, and Gaetani, 2022).…”
Section: Machinery Of Governmentmentioning
confidence: 99%
“…INSTITUTIONAL ARRANGEMENTS FOR PLANNING, BUDGETING, AND TREASURY IN BRAZIL In 2019, Brazil created a new Ministry of Economy by merging five pre-existing institutions, including the Ministries of Finance and of Planning. A 2022 assessment(Mosqueira, Gaetani, and Lafuente, 2022) revealed that the opportunity for linking the budget and treasury with the results framework had been enhanced, and that overall coordination had increased. Still, given the scale of the merger and the distinct administrative cultures of each institution, important challenges remained.…”
mentioning
confidence: 99%
See 1 more Smart Citation